Marketing Mix Analysis of Purchasing Decisions Through the Grabfood Application in Bandar Lampung - Jayadi, Jayadi; Permatasari, Berlintina; Candra, Ade (Universitas Pamulang, 2025)
This research aims to find out how much influence the marketing mix (product, price, place and promotion) has on food purchasing decisions in the Grab Food application. The target population for this research is people who use the Grab Food Application in the city of Bandar Lampung, and the sample took the entire population using a non-probability sampling method. The research results show that the Marketing Mix together has a positive and significant effect on purchasing decisions via the Grabfood application in Bandar Lampung. Based on the table, the coefficient of determination shows an R Square number with a value of 92. This shows that 0.92% of the influence can be explained by the independent variable marketing mix on the dependent variable (purchasing decision), while the remaining 0.8% is explained by other variables that were not tested in this research.